Cyclopropenium Nanoparticles and Gene Transfection in Cells - Steinman, Noam Y. (Pharmaceutics, 2020)
Non-viral vectors for the transfection of genetic material are at the frontier of medical science. In this article, we introduce for the first time, cyclopropenium-containing nanoparticles as a cationic carrier for gene transfection, as an alternative to the common quaternary ammonium transfection agents. Cyclopropenium-based cationic nanoparticles were prepared by crosslinking poly(ethylene imine) (PEI) with tetrachlorocyclopropene. These nanoparticles were electrostatically complexed with plasmid DNA into nanoparticles (~50 nm). Their cellular uptake into F929 mouse fibroblast cells, and their eventual expression in vitro have been described. Transfection is enhanced relative to PEI with minimal toxicity. These cyclopropenium nanoparticles possess efficient gene transfection capabilities with minimal cytotoxicity, which makes them novel and promising candidates for gene therapy.